Analysis and Fabrication of an Active Cooling System for Reducing Photovoltaic Module Temperature - Jakhrani, A. Q.; Jatoi, A. R.; Jakhrani, S. H. (Engineering, Technology & Applied Science Research, 2017)
The purpose of this study is to fabricate and analyze an active cooling system for reducing photovoltaic (PV) module temperature and increasing its efficiency. An active cooling system was devised to cool the PV module. Two modules of same specifications were used for this study. One module was cooled, and other was left un-cooled for performance comparison. Solar radiations, wind speed, ambient temperature and temperatures at different points of the fabricated system were measured. The modules were mounted on a frame facing true south at the inclination of the latitude of the location. The measurements were taken during daytime with one hour intervals for two weeks. The temperatures at various points on cooled and un-cooled photovoltaic modules were noted using two different flow rates with 1 lit/min and 2 lit/min. It was discovered that the efficiency of PV module was enhanced from 6% to 7% during study period. The flow rate of 1lit/min was found more feasible for heat extraction as compared to the flow rate of 2lit/min. The wind speed was found to be more helpful for heat extraction from the modules as compared to other climatic parameters.